2008
DOI: 10.1051/0004-6361:20077946
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the interface between the Local and Loop I bubbles using Strömgren photometry

Abstract: Context. The Sun is located inside an extremely low density region of quite irregular shape called the Local Bubble or Local Cavity. The fraction of this cavity filled with extremely hot gas is known as the Local Hot Bubble. Close to the Local Bubble, there is an even larger cavity known as Loop I. A ring-like feature observed in X-ray and Hi has been proposed as the contour of the bubbles interaction zone around 70 pc. Aims. Our goal is to identify the interface between the Local and Loop I Bubbles and discus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
(89 reference statements)
2
19
0
Order By: Relevance
“…The distance to this interaction region is somewhat uncertain. A recent analysis of the E(b−y) data made by Reis & Corradi (2008) suggests that the western (left) side of the wall is at the distance of 110 ± 20 pc, while the eastern (right) side cannot be seen clearly before 280 ± 50 pc.…”
Section: Interaction Zone Between the Local Bubble And Loop Imentioning
confidence: 99%
“…The distance to this interaction region is somewhat uncertain. A recent analysis of the E(b−y) data made by Reis & Corradi (2008) suggests that the western (left) side of the wall is at the distance of 110 ± 20 pc, while the eastern (right) side cannot be seen clearly before 280 ± 50 pc.…”
Section: Interaction Zone Between the Local Bubble And Loop Imentioning
confidence: 99%
“…The third model, with a globally similar scenario, explains the radio continuum polarization data with two colliding shells, both generated within about the same region as in the Sco-Cen association. Recently, Reis & Corradi (2008), Santos et al (2011) and Reis et al (2011) have questioned the existence of the interaction ring, which is associated to the first model only (see also Frisch et al 2011).…”
Section: On the Shell Geometrymentioning
confidence: 99%
“…However, Egger & Aschenbach's scenario makes no consideration of the kinematics of the H I. Furthermore, their ringlike feature has been questioned (Reis & Corradi 2008). On the other hand, from a detailed study involving about 3900 OB stars Fernández (2005; concluded that the Sco-Cen association could have formed in the Sgr-Car arm and not in the GB.…”
Section: Introductionmentioning
confidence: 99%